The NNER and pre-service teachers' philosophic orientations - Gajda, Rebecca, author; Cobb, R. Brian, advisor (Colorado State University. Libraries, 2001)
The Philosophic Inventory, designed by Robert Leahy, was used to assess the philosophic orientation of pre-service teachers at one National Network for Educational Renewal (NNER) member institution to determine the impact of the teacher licensure program on pre-service teacher beliefs. Results indicate significant philosophical shifts in pre-service teacher beliefs over the course of the teacher licensure program toward the democratic domains of progressivism and existentialism. However, multiple ANOVAs revealed significant interaction effects between gender and philosophic orientation that suggest gender has a profound impact on the formation of one's philosophic orientation. In addition to quantitative survey analysis, six pre-service teachers were interviewed. Focus group examination suggests that many pre-service teacher beliefs about schooling mirror the public at large and do not fully reflect the mission of the NNER.
Keywords: teacher education; educational philosophy